Evaluation of the Drying Process of Grape cv. Arra 15® (Research, Society and Development, 2021)
The Brazil is a country where there is a great diversity of fruits, with an emphasis on grape growing, especially in the northeast region, but due to the high export of fruit, much of it considered improper is discarded. Therefore, this study aimed to elaborate raisin grape of cv. Arra 15'® from the drying in oven and air fryer with the application of a chemical pre-treatment, and to characterize how much the physical-chemical properties. The grapes in natura were pre-treated with NaOH 1% to 95 ºC for 30 seconds, dried in oven and air fryer. The fruit was characterized as to humidity, total soluble solids, pH, total acidity and color. The drying processes used reduced the humidity, thus obtaining the raisin. The logarithm model was better adjusted to the experimental data. With the increase in temperature there was an increase in diffusivity, and from the analytical solution of the diffusion equation presented low values of Biot number, indicating that the boundary condition used (third type) did not describe the process satisfactorily. With this, we conclude that these results are important because they demonstrate that the processing was efficient and made it possible to obtain the raisin with good nutritional characteristics.